Study on biological characteristics of Macrobrachium sp. at the trian reservoir, Dong Nai province - Binh, Le Thi; Thu Huong, Do Thi (Academia Journal of Biology, 2014)
Macrobrachium sp. (Palaemonidae) is one shrimp species having a quite high yield at the Trian reservoir, Dongnai province. It has small sizes; its average length and its weight oscillate from 28 to 52mm and 0.28 to 1.8 g, respectively. This species is the same as M. pilimanus (De Man, 1879) and M. dienbienphuense (Dang et Nguyen Huy, 1972) in shape. Its II pereiopods are bigger than the others. Its left and right II pereiopods are different in size but the same in shape. Numerous tufts of long soft hairs are present on the entire surface of the fingers, such long and soft hairs also are present on the outer surface of the palm. Its hatching time is around 24-26 days (the water temperature varied between 260 and 27oC; DO: 4-5 mgO2/L; hardness: 81 mg/L CaCO3 and pH: 6.5-7). Its eggs are oval in shape, heavy green in color and the sizes of its eggs are about 1.4 x 1.8 mm. Its fecundity is 143 ± 6.75 eggs/g of body weight. The amount of eggs is 67 ± 5.63 eggs per individual and its real fecundity is 94 ± 5.62 larvae/g of body weight. Its six-day old larva are able to move to the bottom for living. Macrobrachium sp. is able to spawn throughout the year. Macrobrachium sp. is an omnivorous species and also like eating small aquatic plants, organic matter.